2020
DOI: 10.1242/jcs.241505
|View full text |Cite
|
Sign up to set email alerts
|

EML4–ALK V3 oncogenic fusion proteins promote microtubule stabilization and accelerated migration through NEK9 and NEK7

Abstract: EML4-ALK is an oncogenic fusion present in ∼5% of non-small cell lung cancers. However, alternative breakpoints in the EML4 gene lead to distinct variants of EML4-ALK with different patient outcomes. Here, we show that, in cell models, EML4-ALK variant 3 (V3), which is linked to accelerated metastatic spread, causes microtubule stabilization, formation of extended cytoplasmic protrusions and increased cell migration. EML4-ALK V3 also recruits the NEK9 and NEK7 kinases to microtubules via the N-terminal EML4 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…The role of NEK9 in regulating microtubules may be directly related to its involvement in some types of cancer. A recent study showed that EML1-ALK variant 3, an oncogenic fusion present in non-small cell lung cancers, allows the recruitment of NEK9 and NEK7 proteins to microtubules via the N-terminal EML4 microtubule-binding region, leading to microtubule stabilization and increasing cell migration [187]. Beyond that, an elevation in NEK9 expression was associated with a reduction in progression-free survival in EML4-ALK patients.…”
Section: Nek9mentioning
confidence: 99%
“…The role of NEK9 in regulating microtubules may be directly related to its involvement in some types of cancer. A recent study showed that EML1-ALK variant 3, an oncogenic fusion present in non-small cell lung cancers, allows the recruitment of NEK9 and NEK7 proteins to microtubules via the N-terminal EML4 microtubule-binding region, leading to microtubule stabilization and increasing cell migration [187]. Beyond that, an elevation in NEK9 expression was associated with a reduction in progression-free survival in EML4-ALK patients.…”
Section: Nek9mentioning
confidence: 99%
“…Initially, NEK7 was thought to be the downstream target of WHSC1L1 involved in human carcinogenesis through expression profile analysis in vitro using human bladder and lung cancer cell lines (Kang et al, 2013). Similarly, in a recent study, EML4-ALK variant 3(V3) was proposed to mediate microtubule stabilization through NEK7 and NEK9, accelerating cell migration in EML4-ALK lung cancer (O'Regan et al, 2020). Another study found NEK7 is probably a downstream target gene of WHSC1 in multiple squamous cell carcinoma of the head and neck (SCCHN) cell lines as indicated via microarray expression profile analysis (Saloura et al, 2015).…”
Section: Nek7-regulated Mitosis and Nlrp3 Inflammasome In Diseases DImentioning
confidence: 99%
“…Accumulating data from several retrospective analyses [ 23 , 24 , 94 , 95 , 96 , 97 ] and the randomized phase 3 study ALTA-1L [ 98 ] show that the “short” EML4-ALK fusion variant 3 (E6:A20, Figure 1 b) is associated with earlier treatment failure and shorter survival regardless of the type of treatment. V3-positive cases comprise approximately one-third of all ALK + NSCLC and present with more aggressive disease already at baseline, as evident by a higher number of metastatic sites at initial diagnosis [ 22 , 23 , 24 , 99 ]. Biochemical basis for this adverse clinical phenotype is the higher stability of shorter EML4-ALK variants, which leads to accumulation and stronger oncogenic signaling, as well as their better interaction with the cytoskeleton, which increases the migratory capacity of V3-positive cancer cells [ 22 , 100 ].…”
Section: State-of-the-art After the First Linementioning
confidence: 99%